Women's studies in India : some perspectives - Krishna Raj, Maithreyi; Shreemati Nathibai Damodar Thackersey Women's University. Research C entre for Women's Studies (Bombay : Popular Prakashan, 1986)
Lectures delivered at a winter institute, organized by the Research Centre for Women's Studies, S.N.D.T. Women's University, for the prepar ation of curriculum and teacher training in women's studies.
Includes bibliographical references.
Keywords: Women's studies -- India